A cognitive model of perceptual path planning in a multi-robot control system - Reitter, D.; Lebiere, C.; Lewis, M.; Huadong Wang; Zheng Ma (2009 IEEE International Conference on Systems, Man and Cybernetics, 2009)
We discuss an experiment involving visual path planning for multiple, remote robots in a partially visible building, with a partial 2D map available. Participants in the experiment defined waypoints for each robot to circumnavigate obstacles and explore the building. A cognitively plausible model of visual planning is evaluated using a normalized metric of the fit between model and subject itineraries. We discuss variation in the data and model fit, indicating individual differences in strategies to cope with task demands.